2018
DOI: 10.3390/w10101488
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Accumulative Characteristics of Dissolved Heavy Metals in Modified Bioretention Media

Abstract: Twelve bioretention filter columns with different media were designed to study the effects of media on dissolved heavy metals in bioretention systems by changing three test conditions (inflow concentration, discharge ratio, and recurrence interval). The results showed that the average load reduction efficiency of the bioretention soil media (BSM)+10%water treatment residue, BSM+10%green zeolite, and BSM+10%medicinal stone for Cu and Zn was larger than 80%. The highest volume reduction efficiency is 39.25% by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The only variable considered was the plant. Previous studies have shown that metal distribution in vegetative systems is affected by some other factors such as inflow concentration, discharge ratio and recurrence interval on metals accumulation [43]. It was found that heavy metals are mostly accumulated in soils and roots.…”
Section: Cadmiummentioning
confidence: 98%
“…The only variable considered was the plant. Previous studies have shown that metal distribution in vegetative systems is affected by some other factors such as inflow concentration, discharge ratio and recurrence interval on metals accumulation [43]. It was found that heavy metals are mostly accumulated in soils and roots.…”
Section: Cadmiummentioning
confidence: 98%
“…In an effort to optimise plant biofilters, the introduction of engineered growth media such as zeolite (see Li et al 2014), perlite (see Le Coustumer et al 2012) and vermiculite (see Li et al 2018) in combination with traditional loamy sand as a carbon source (see Bratieres et al 2008) may potentially increase stormwater remediation efficacy and biofilter longevity (Chandrasena et al 2017). It is therefore important to not only optimise growth media, but also to consider the effects of the media on plant health and vitality (Malézieux et al 2007).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%